Aminoglutethimide induced hormone suppression and response to therapy in advanced postmenopausal breast cancer. - Harris, A. L. (Nature Publishing Group, 1983)
Eighty-one postmenopausal women with advanced breast cancer were studied for the effects of treatment with aminoglutethimide (AG) plus hydrocortisone on peripheral hormones and response to therapy. There were 40 responders (R) and 41 non-responders (NR) at 3 months from the start of treatment. Plasma oestrone concentrations were higher in non-responders at 1 and 2 months after starting AG (Means: NR 106 +/- 50, R 84 +/- 26 pmol l-1, P less than 0.05; highest value NR 121 +/- 51, R 99 +/- 24 pmol l-1, P less than 0.05). High oestrone levels were correlated with bulky liver secondaries, but not with age, tumour-free interval, time from last menstrual period, time from relapse to start of AG or body weight. Non-responders had higher mean prolactin levels on treatment (prolactin less than 500 mIUl-1 in 14/40 NR, 2/35 R, P less than 0.01). High oestrone or prolactin levels were present in 28/41 NR and 6/40 R (P less than 0.001). Dehydroepiandrosterone sulphate suppression did not differ between R and NR. The differences in peripheral endocrine environment in non-responding patients suggest that oestrogen metabolism may differ in non-responding patients and that sub-groups could be selected for rational endocrine therapy.